Variability in short and long-term seed dormancy in clover plants from a single population - Norman H.C.; Cocks P.S.; Galwey N.W.; Osman A.E. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Plants of the same species of clover (Trifolium spp.) from the same site of collection may differ in dormancy strategies. Variation within a population was found in the level of hardseededness both at maturity and after 6 months on the soil surface, and in the half-life of hard seed breakdown. This variation may allow for a particular dormancy pattern to be easily selected by agronomists without the need for extensive germplasm collection.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)